2014 18th International Conference on System Theory, Control and Computing (ICSTCC) 2014
DOI: 10.1109/icstcc.2014.6982445
|View full text |Cite
|
Sign up to set email alerts
|

Model predictive control and fuzzy control in a hierarchical structure for wastewater treatment plants

Abstract: This paper presents a hierarchical two-level control structure for a biological wastewater treatment plant (WWTP), with the goal of simultaneously improving the effluent quality and reducing operational costs. The Benchmark Simulation Model No.1 is used as working scenario.The idea is to adjust the dissolved oxygen in the fifth tank (DO5) according with the present working conditions, instead of keeping it in a fixed value. Thus is concreted by a hierarchical structure. MPC with inlet flow rate feedforward con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In [18] a modified version of GPC algorithm based on a positional form for both the process model and controller cost function is presented. In this paper only the cost function (13) is considered in the positional form and the CARIMA process model is considered. Thus, the minimization of the cost function (13) with the output of the controller replaced by u(t)=u(t-1)+Δu(t) where u(t-1) is known (u (t-1)=u') leads to:…”
Section: Modified Gpc Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In [18] a modified version of GPC algorithm based on a positional form for both the process model and controller cost function is presented. In this paper only the cost function (13) is considered in the positional form and the CARIMA process model is considered. Thus, the minimization of the cost function (13) with the output of the controller replaced by u(t)=u(t-1)+Δu(t) where u(t-1) is known (u (t-1)=u') leads to:…”
Section: Modified Gpc Algorithmmentioning
confidence: 99%
“…Thus, optimizing the aeration process actually means determining the optimal value of the dissolved oxygen setpoint. Several strategies have been proposed and Model Predictive Control (MPC) proved to be a suitable one [12,13,14]. Due to specific features of WWTP a two-layer hierarchical structure is developed: local process control loops as a lower layer and a higher layer of process optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of strong disturbances in WWTPs, MPC has difficulties in keeping the controlled variables at their reference level. To compensate the disturbances, a feedforward control is added, as in refs and . MPC provides options for the feedforward compensation of the measured disturbances, in the same way as for the reference signals.…”
Section: Control Configuration For the Proposed Objectivesmentioning
confidence: 99%
“…On the contrary, when NH decreases, less DO is required, producing less NO. NH5 is not forced to keep a fixed value since it has been observed that it is not possible by manipulating the DO set point due to the large disturbance , .…”
Section: Control Configuration For the Proposed Objectivesmentioning
confidence: 99%
See 1 more Smart Citation